Unraveling the Light‐Induced Degradation Mechanisms of CH3NH3PbI3 Perovskite Films - Nickel, Norbert H.; Lang, Felix; Brus, Victor V.; Shargaieva, Oleksandra; Rappich, Jörg (Advanced electronic materials, 2017)
Organic–inorganic perovskite solar cells have experienced a remarkable development. In a short period of time power conversion efficiencies have jumped to values of more than 22%. However, the stability of these devices is an important subject. The stability of CH3NH3PbI3 perovskite films is investigated using visible and ultraviolet light in oxygen atmosphere and in vacuum. Illumination in O2 atmosphere results in a swift degradation. Oxygen acts as a catalyst decomposing methylammonium ions (CH3NH3+) into CH3NH2 and hydrogen. In vacuum, another degradation mechanism is observed. Prolonged illumination of the samples with photons from blue and UV light‐emitting diodes also results in dissociation of the methylammonium ion into CH3NH2 and hydrogen. In both cases the resulting molecules are highly mobile at room temperature and diffuse out of the samples. The light‐induced dissociation of CH3NH3+ is accompanied by the generation of localized defects in the band gap of the perovskite. Furthermore, the experimental data clearly show that the molecular orbitals of CH3NH3+ are not in resonance with the energy bands of the perovskite lattice. Light‐induced degradation of methylammonium (MA) lead iodide in oxygen atmosphere and in vacuum is investigated. Isotope experiments show that O2 acts as a catalyst decomposing MA ions into CH3NH2 and hydrogen. Experimental evidence of a hitherto unknown degradation mechanism due to an exposure to visible and ultraviolet light is presented. This degradation mechanism does not require the presence of oxygen.